Nomenclatural notes on Eugenia with closed calyces: Calycorectes O.Berg and Mitranthes O.Berg (Myrtaceae) - Giaretta, Augusto; Lucas, Eve; Souza, Marcelo Da Costa; Mazine, Fiorella Fernanda; Sano, Paulo Takeo (Phytotaxa, 2018)
This study incorporates results of the latest phylogenetic framework to support nomenclatural adjustment in Eugenia, including to its circumscription with regard to the genera Calycorectes and Mitranthes. Five synonyms, two new names and one new combination in Eugenia are provided; a pre-existing name for a Eugenia section is re-established.